Mengembangkan Misi Gereja dalam Bingkai Moderasi Beragama - Carolina Etnasari Anjaya; Yonatan Alex Arifianto (THRONOS: Jurnal Teologi Kristen, 2021)
Religious moderation is a demand for all elements of society to carry it out, including churches and believers. The actualization of religious moderation that has been implemented by the church needs to fulfill the mission principle in accordance with the teachings of the Bible. This research aims to provide a new paradigm about religious moderation in the context of the church's mission and how the church practices it. The research method uses a qualitative descriptive model approach. Data collection was obtained through a study of the relevant literature. The research yields the result that religious moderation in the context of the church's mission is based on the main principle: peace. The church needs to carry out its mission within the framework of religious moderation by fulfilling the peacemaker principle. Its actualization can be applied in four ways. Act as a witness of God who dares to express his identity as a disciple of Christ amid a pluralistic society. Next, the church needs to rise to become a solution or a solution provider in social problems regardless of differences through collaboration. Therefore, the church formed various Christian communities to build a common culture in society. The community can synergize with other communities outside of Christianity. The latter conduct dialogue word between church denominations to create unity of heart in conveying the truth of God.AbstrakModerasi beragama menjadi tuntutan bagi seluruh elemen masyarakat untuk menjalankannya, termasuk gereja dan umat percaya. Aktualisasi moderasi beragama yang selama ini diterapkan oleh gereja perlu memenuhi prinsip misi yang sesuai dengan ajaran Alkitab. Riset ini bertujuan memberikan paradigma yang baru mengenai moderasi beragama yang dipandang dari konteks misi gereja dan bagaimana gereja mempraktikannya.  Metode riset mempergunakan pendekatan kualitatif model deskriptif. Pengumpulan data didapatkan melalui studi literatur yang relevan. Riset memberikan hasil yaitu bahwa moderasi beragama dalam konteks misi gereja dilandasi oleh prinsip utama: kedamaian. Gereja perlu menjalankan misi dalam bingkai moderasi beragama dengan memenuhi prinsip pembawa damai. Aktualisasinya dapat diterapkan melalui empat hal. Bertindak sebagai saksi Tuhan yang berani mengekspresikan identitas sebagai murid Kristus di tengah-tengah kemajemukan masyarakat. Selanjutnya gereja perlu bangkit menjadi solusi atau pemberi solusi dalam permasalahan sosial tanpa memandang perbedaan melalui kolaborasi. Oleh karena itu, gereja membentuk pelbagai komunitas Kristen untuk membangun budaya bersama dalam masyarakat. Komunitas dapat bersinergi dengan komunitas lain di luar Kristen. Yang terakhir melakukan dialog antar denominasi gereja agar tercipta kesatuan hati dalam menyampaikan kebenaran firman Tuhan.